Analysis of Corporate Governance and Cost of Equity (Case Study of Textile Industry on BEI 2018-2019) - Novia Rahmadani; Estu Widarwati (STIESA Press, 2021)
The study aims to describe the Corporate Governance and Cost of Equity of textile industry of Indonesia listed IDX in 2018-2019. The study was conducted descriptively, and secondary data was collected based on a review of documents sourced from annual report of Industry Tekstile. Analyzed data show governance of textile industry. Furthermore, the study find a positive trend between corporate governance and cost of equity in textile industry